Korpus Linguistik Copula Sebagai Database Tulisan Mahasiswa Bahasa Jerman Level A1-B1 - Edy Hidayat; M. Kharis; Herri Akhmad Bukhori; Dewi Kartika Adiyani; Rizky Ardiansyah; Ivan Abdurrafie (Universitas Nahdlatul Ulama Blitar, 2026)
The existence of a web-based corpus of German texts created by students is crucial for both lecturers and students, as this corpus can be utilized as initial data for all research on German text writing skills. With a web-based platform, users can access the corpus in the form of a search engine, vocabulary list, word relevance, and frequency. Through the corpus database, lecturers and students can conduct research and observe patterns in students' ability to write German texts. The data collected in this study consists of student-written texts uploaded and stored in the system's database. This collection of texts is referred to as a journal. The journal data is used for the corpus system, which will be analyzed. In recent years, language teachers, particularly foreign language instructors, have had to incorporate corpora into their teaching. Through this corpus database, lecturers and students can conduct research and observe patterns in students' ability to write German texts.